Characterization of the Penetration of the Blood–Brain Barrier by High-Performance Liquid Chromatography (HPLC) Using a Stationary Phase with an Immobilized Artificial Membrane. (13th October 2018) - Doležal, Rafael; Karásková, Natálie; Musil, Karel; Novák, Martin; Maltsevskaya, Nadezhda V.; Maliňák, Dávid; Kolář, Karel; Soukup, Ondřej; Kuča, Kamil; Žďárová Karasová, Jana
ABSTRACT: The biological activity of drugs on organisms is associated with the pharmacokinetic properties, such as the ability to penetrate through environments of varying polarity such as cellular organelles. In this area, particular attention is turned to the physicochemical properties that determine the potential of drugs to pass across the blood–brain barrier and thus to act on the central nervous system. In this study, special effort has been devoted to the simulation of passive diffusion of seven drugs (propranolol, ibuprofen, atenolol, promazine, chlorpromazine, imipramine, and desipramine) through the blood–brain barrier by high-performance liquid chromatography (HPLC) using a column with an immobilized artificial membrane. Gradient reverse elution was used to develop a linear correlation model for the capacity factors k IAM and the in vivo logarithmic values of brain-to-blood drug concentration ratios (log BB ) with R of 0.9851. Eleven additional pharmaceuticals were determined by the same method to predict their potential to penetrate the blood–brain barrier. The reported analytical method represents an alternative tool for rapid and noninvasive assessment of the absorption properties of chemicals, especially for the development of novel drugs. The retention of the studied compounds on the immobilized artificial membrane column was also compared with three other C18-based stationary phases. Herein, the results of the HPLC determination of drugs using an immobilized artificial membrane are briefly discussed with respect to a general application of the method for evaluating a broader spectrum of pharmaceutical compounds.